تأثير درجات الحرارة الثابتة في بعض المؤشرات الحياتية للمتطفل Encyrtus aurantii (Geoffroy) (Hymenoptera: Encyrtidae) مخبرياً. - محمد, إياد محمد; بشير, عبد النبي محمد; أبو كف, نبيل (Latakia University Journal -Biological Sciences Series, 2013)
دُرست حياتية المتطفل Encyrtus aurantii (Geoffroy) (Hymenoptera: Encyrtidae) مخبرياً عند درجات الحرارة 18، 21، 24، 27، 30 مْ ورطوبة نسبية 65± 5% وفترة إضاءة (16:8) سا (ظلام: إضاءة). تمت تربية المتطفل على حشرة الحمضيات القشرية البنية الرخوة Coccus hesperidum Linnaeus المرباة على القرع العسلي Cucurbita moschata. بينت النتائج أن أطول فترة حياة للوصول من البيضة إلى طور العذراء كانت على درجة حرارة 18مْ بمتوسط 24.25 يوماً، وأقل فترة كانت على درجة الحرارة 30 مْ بمتوسط 8.25 يوماً، وكانت أطول فترة للتطور من طور العذراء حتى انبثاق الحشرة الكاملة على درجة حرارة 18 مْ بمتوسط 10.75 يوماً، و أقل فترة على درجة الحرارة 30 مْ بمتوسط 5.5 يوماً. كانت أطول فترة للتطور من طور البيضة وحتى انبثاق الحشرة الكاملة على درجة الحرارة 18 مْ بمتوسط 35 يوماً، وأقلها على درجة الحرارة 30مْ بمتوسط 13.75 يوماً. وكانت العتبة الحرارية الدنيا (LDT) من البيضة حتى العذراء 15.83 مْ، ومن العذراء حتى انبثاق الحشرة الكاملة 13.43 مْ، وللجيل الكامل 16.95مْ. ويحتاج المتطفل إلى مجموع درجات حرارة فعّالة (SET) 122.74 درجة- يومية فوق العتبة الحرارية الدنيا (16.95) لإتمام جيل واحد (من البيضة إلى البالغة). Some biological parameters of the parasitoid, Encyrtus aurantii (Geoffroy) (Hymenoptera : Encyrtidae) were studied under controlled laboratory conditions at five levels of temperature 18, 21, 24, 27, and 30 °C, 65±5% R.H. and a photoperiod of 16:8 (L:D) h when reared on Brown soft scale Coccus hesperidum L. (Homoptera: Coccidae) reared on Pumpkin Cucurbita moschata during the season 2010- 2011 . Result showed that the longer developmental period from egg to pupa was on 18 °C with an average of 24.25 days, and the lower developmental period was on 30°C with an average of 8.25 days. The longer developmental period from pupa to adult was on 18 °C with an average of 10.75 days, and the lower period was on 30 °C with an average of 5.5 days. The lower developmental threshold (LDT) from egg to pupa was 15.83°C, and 14.34°C from pupa to adult. E. aurantii required a Sum of Effective Temperatures (SET) of 122.74 degree-days above the lower developmental threshold (16.95 °C) to complete the development from egg to adult.